2021
DOI: 10.1292/jvms.20-0592
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ear skin swabs for monitoring methicillin-resistant <i>Staphylococcus aureus</i> ST398 in pigs at abattoirs

Abstract: Monitoring the prevalence of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) in pigs could be useful for managing transmission risk to humans. To optimize sampling for LA-MRSA monitoring, we compared the sensitivity of MRSA isolation from skin swabs taken behind the ear and nasal swabs collected from 276 pigs and investigated the prevalence of MRSA in their carcasses. MRSA was isolated from 40 behind the ear skin swabs (14.5%), which was statistically higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…A greater level of agreement (0.7; good agreement) had been indicated between these sample types from a comparative farm study [ 22 ]. However, a similar level of agreement (0.4; moderate) had been shown by a previous abattoir study which assessed individual pigs [ 23 ], and this may indicate the importance of collecting both sample types from pigs to maximise the ability to detect MRSA at slaughter.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A greater level of agreement (0.7; good agreement) had been indicated between these sample types from a comparative farm study [ 22 ]. However, a similar level of agreement (0.4; moderate) had been shown by a previous abattoir study which assessed individual pigs [ 23 ], and this may indicate the importance of collecting both sample types from pigs to maximise the ability to detect MRSA at slaughter.…”
Section: Discussionsupporting
confidence: 71%
“…The relative sensitivity of different sampling sites in pigs and on farms has been investigated [21][22][23]. These investigations found that sampling both nasal swabs and ear skin swabs had a higher relative sensitivity (98.2%) than sampling either site alone, or sampling perineum, or other combinations of these three sites.…”
Section: Introductionmentioning
confidence: 99%
“…Ears contaminated with ST398 MRSA originated from pigs in the Tohoku and Kanto regions. In contrast to the characteristics of ST398 MRSA reported in the two regions [ 20 , 21 , 22 ], the characteristics of the isolates in the present study were different. Fifty-eight ST398 MRSA isolates were obtained in the Kanto region between 2012 and 2014, and the most frequent spa type was t16450 (33 isolates), followed by t034 (14 isolates), and t3934 (11 isolates) [ 20 ].…”
contrasting
confidence: 99%
“…The core-genome phylogenetic analysis showed relatively small numbers of single nucleotide polymorphisms (SNPs) (range, [13][14][15][16][17][18][19][20][21][22][23][24][25][26] in the seven ST398 MRSA isolates (a-1, a-2, b-1, c-1, d-1, e-1, and f-1) carrying SCCmec type IVd (Fig. 1).…”
mentioning
confidence: 99%
“…The geographic range of LA-MRSA ST398 is expanding. It has been reported in pigs and humans in recent years in Korean and Japan ( Lee et al, 2021 ; Nakaminami et al, 2021 ; Sasaki et al, 2021 ). LA-MRSA ST398 isolates were recovered from milk samples from two farms in China in one study.…”
Section: Concentrated Animal Feeding Operations and Transmission Of M...mentioning
confidence: 94%